Continuity of certain pseudodifferential operators in spaces of generalized smoothness - Knopova, V.P. (Український математичний журнал, 2006)
We investigate the continuity of a pseudodifferential operator in some spaces of generalized smoothness. Some properties of spaces of generalized smoothness and generalized Lipschitz spaces are established. Досліджено неперервність псевдодиференціального оператора у деяких просторах узагальненої гладкості. Доведено деякі властивості просторів узагальненої гладкості та узагальнених просторів Ліпшиця.